2014
DOI: 10.1007/s11356-014-2834-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of nine selected emerging trace organic contaminants in an artificial recharge system supplemented with a reactive barrier

Abstract: Artificial recharge improves several water quality parameters, but has only minor effects on recalcitrant pollutants. To improve the removal of these pollutants, we added a reactive barrier at the bottom of an infiltration basin. This barrier contained aquifer sand, vegetable compost, and clay and was covered with iron oxide dust. The goal of the compost was to sorb neutral compounds and release dissolved organic carbon. The release of dissolved organic carbon should generate a broad range of redox conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…The barrier comprises vegetable compost and aquifer sand in equal volumetric proportions and a very small fraction of clay and iron oxides. The vegetable compost aimed to release dissolved organic carbon into the infiltrating water to favor a broad range of redox conditions below the basin, thus increasing the diversity of microbial metabolic paths to enhance removal of organic contaminants (Li et al, 2013;Alidina et al, 2014;Valhondo et al, 2014Valhondo et al, , 2015. Clay and iron oxide were added to provide sorption sites for cationic and anionic organic compounds, respectively.…”
Section: Site Description and Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations
“…The barrier comprises vegetable compost and aquifer sand in equal volumetric proportions and a very small fraction of clay and iron oxides. The vegetable compost aimed to release dissolved organic carbon into the infiltrating water to favor a broad range of redox conditions below the basin, thus increasing the diversity of microbial metabolic paths to enhance removal of organic contaminants (Li et al, 2013;Alidina et al, 2014;Valhondo et al, 2014Valhondo et al, , 2015. Clay and iron oxide were added to provide sorption sites for cationic and anionic organic compounds, respectively.…”
Section: Site Description and Instrumentationmentioning
confidence: 99%
“…Clay and iron oxide were added to provide sorption sites for cationic and anionic organic compounds, respectively. Details on the barrier are provided by Valhondo et al (2014Valhondo et al ( , 2015.…”
Section: Site Description and Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that the reactive barrier enhanced the removal of some emergent contaminants, such as sulfamethoxazole or caffeine (Valhondo et al, 2014). More information about the site and the performance of the reactive barrier can be found in Valhondo et al (2014).…”
mentioning
confidence: 99%